How Safe are Fluoroquinolones for Diabetic Patients? A Systematic Review of Dysglycemic and Neuropathic Effects of Fluoroquinolones - Althaqafi A; Ali M; Alzahrani Y; Ming LC; Hussain Z (Dove Medical Press, 2021)
Abdulrhman Althaqafi,1,* Majid Ali,2 Yusuf Alzahrani,3 Long Chiau Ming,4,* Zahid Hussain5 1Department of Pharmacy, Al-Noor Hospital, Makkah, Saudi Arabia; 2College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 3College of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 4PAPRSB Institute of Health Sciences, Universiti Brunei Darussalam, Gadong, Brunei Darussalam; 5Faculty of Health, University of Canberra, Canberra, ACT, Australia*These authors contributed equally to this workCorrespondence: Majid Ali; Zahid Hussain Email maaali@uqu.edu.sa; zahid.hussain@canberra.edu.auIntroduction: The US Food and Drug Administration issued safety warnings about neuropathy in 2013 and dysglycemia in 2018 caused by fluoroquinolone use, mainly based on case reports and case series. We conducted this systematic review to evaluate the safety of fluoroquinolones in diabetic patients by investigating their dysglycemic and neuropathic effects.Methods: PubMed, Scopus, and Google Scholar were searched for randomized controlled trials and observational studies published from inception till September 2019 evaluating the safety of fluoroquinolones. Efficacy studies of fluoroquinolones reporting these adverse effects were also included. Primary outcomes were hypoglycemia, hyperglycemia, and neuropathy among patients with or without diabetes and treated with fluoroquinolones compared with placebo or other antibiotics. The Cochrane Collaboration tool for randomized controlled trials and modified Newcastle-Ottawa quality-assessment scale were used for assessment of the included studies.Results and Discussion: A total of 725 studies were identified in the initial search. After screening of titles and abstracts and full-text review, 16 articles fulfilled the inclusion criteria. The sampled patients were aged 30- 78 years. Hyperglycemia was reported in 1,588 patients that received fluoroquinolone among eight studies with 4,663 patients, and hypoglycemia was reported in 2,179 patients that received fluoroquinolones among eleven studies with 6,208 patients. Dysglycemia was not generally associated with diabetes mellitus per se. Nevertheless, patients with more comorbidities, especially those with chronic kidney disease, receiving antidiabetics and/or steroids had more glycemic events when treated with fluoroquinolones.Conclusion: Moxifloxacin was found to be associated the most and ciprofloxacin the least with dysglycemia. fluoroquinolones must be used with great caution among diabetic patients who have comorbidities and are receiving antidiabetics and/or steroids. Further evidence is required from studies on neuropathy caused by fluoroquinolones.Keywords: gatifloxacin, moxifloxacin, ciprofloxacin, levofloxacin, hyperglycemia, hypoglycemia, safety, adverse drug reaction